Kualitas Minyak Blend Kelapa Kopra dan Minyak Kelapa Sawit ditinjau dari Kadar Air, Kadar Asam Lemak Bebas dan Bilangan Peroksida - Febliza, Asyti; Okatariani, Oktariani; Putri, Aisyah Meisya (Jurnal Riset Kimia, 2020)
This research examined the quality of edible oil from Crude Coconut Oil (CCO) and Palm Coconut Oil (PCO) and their blends with CCO : PCO proportional was about 40:60 and 60:40, respectively. The quality of these samples was based on water proportion, free fatty acid (FFA) and peroxide value (PV) contained. This study was conducted to improve the quality of edible oil. SNI 3741-2013 was used as method of this research, which the result compared with the SNI standard for edible oil. Results of this research for water proportion in oil samples PCO, CCO, CCO (40) : PCO (60) and CCO (60):PCO  (40)  in  order  were  0.000122; 0.010905; 0.001878; 0.030996. The FFA proportions for them were 0.02; 0.01; 0.02; 0.02 and PV values were 7.10; 3.00; 6.10; 5.10, respectively. From this result, we can conclude that all samples had good quality for water proportion and FFA, except for peroxide value (PV) mark which had the higher mark compared to the SNI standard. We also concluded that CCO became the best quality of edible oil compared to others.